Physiological symmetry of transcranial magnetic stimulation‐evoked EEG spectral features. Issue 18 (21st July 2022) - D'Ambrosio, Sasha; Jiménez‐Jiménez, Diego; Silvennoinen, Katri; Zagaglia, Sara; Perulli, Marco; Poole, Josephine; Comolatti, Renzo; Fecchio, Matteo; Sisodiya, Sanjay M.; Balestrini, Simona
Abstract: Transcranial magnetic stimulation (TMS)‐evoked EEG potentials (TEPs) have been used to study the excitability of different cortical areas (CAs) in humans. Characterising the interhemispheric symmetry of TMS‐EEG may provide further understanding of structure–function association in physiological and pathological conditions. We hypothesise that, in keeping with the underlying cytoarchitectonics, TEPs in contralateral homologous CAs share similar, symmetric spectral features, whilst ipsilateral TEPs from different CAs diverge in their waveshape and frequency content. We performed single‐pulse (<1 Hz) navigated monophasic TMS, combined with high‐density EEG with active electrodes, in 10 healthy participants. We targeted two bilateral CAs: premotor and motor. We compared frequency power bands, computed Pearson correlation coefficient ( R ) and Correlated Component Analysis (CorrCA) to detect divergences, as well as common components across TEPs. The main frequency of TEPs was faster in premotor than in motor CAs ( p  < .05) across all participants. Frequencies were not different between contralateral homologous CAs, whilst, despite closer proximity, there was a significant difference between ipsilateral premotor and motor CAs ( p  > .5), with frequency decreasing from anterior to posterior CAs. Correlation was high between contralateral homologous CAs and low between ipsilateral CAs. When applying CorrCA, specific components were shared by contralateral homologous TEPs. We show physiological symmetry of TEP spectral features between contralateral homologous CAs, whilst ipsilateral premotor and motor TEPs differ despite lower geometrical distance. Our findings support the role of TEPs as biomarker of local cortical properties and provide a first reference dataset for TMS‐EEG studies in asymmetric brain disorders. Abstract : TMS‐evoked potentials from homologous cortical areas share similar spectral features, whilst TMS‐evoked potentials from ipsilateral cortical areas have different spectral features. TMS can be used as a potential biomarker to assess cortical functions.